Transformation of internet addiction on the background of social isolation and security crisis - Stolyarenko, A. M.; Horodokin, A. D.; Столяренко, Андрій Миколайович; Городокін, Антон Дмитрович (My University, 2023)
Aim — based on the analysis of the characteristics of Internet addiction, identify its peculiarities on the background of social isolation and security crisis. Materials and methods. The study was conducted on a contingent of 120 respondents (students of higher education) aged 18 to 23, who have experience of permanent stay in conditions of social isolation in Ukraine (2020—2023), with established Internet-addiction according to Internet Addiction Test (K. Young, 1998) and Internet Use Disorders Identification Test (Linskiy I. V., Minko A. I., Artemchuk A. P. et al., 2009). The distribution of the contingent by gender was symmetrical. The research method is a structured psychological interview. Study results. In our analysis, it becomes evident that the excessive utilization of the Internet does not merely align with a series of non-chemical addictions; rather, it operates as a facilitative mechanism for a broad range of behavioral and psychological transgressions, which arise as an interconnected functional entity. Within this multifaceted spectrum, we discern two discrete categories: the formation of compulsive behavior patterns and the justification of pre-existing behavior abnormalities. Мета — на ґрунті аналізу характеристик Інтернет-залежності виявити її особливості на тлі соціальної ізоляції та кризи безпеки в Україні. Дослідження проводили на контингенті 120 осіб (здобувачі вищої освіти) віком від 18 до 23 років, які мають досвід постійного перебування в умовах соціальної ізоляції в Україні (2020—2023 рр.), із встановленою Інтернет-залежністю відповідно до Тесту на Інтернет- залежність (К. Янг, 1998) та Тесту ідентифікації розладів використання Інтернету (Лінський І. В., Мінко А. І., Артемчук А. П. та ін., 2009). Розподіл контингенту за статтю був симетричним. Метод досліджування — структуроване психологічне інтерв'ю. У нашому аналізі стає очевидним, що надмірне використання Інтернету — не просто пов'язане з рядом нехімічних залежностей; фактично воно є механізмом реалізації широкого діапазону поведінкових і психологічних порушень, які виникають як взаємопов'язана функціональна сутність. У цьому спектрі ми розрізняємо дві окремі категорії: формування компульсивних патернів поведінки та виправдання наявних аномалій поведінки.
Трансформація інтернет-залежності на тлі соціальної ізоляції та кризи безпеки*
Keywords: Internet; addiction; Internet addiction; compulsions; behavior violations; Інтернет; залежність; Інтернет-залежність; компульсії; порушення поведінки